2007
DOI: 10.1002/jobm.200610207
|View full text |Cite
|
Sign up to set email alerts
|

Esterases and putative lipases from tropical isolates of Aureobasidium pullulans

Abstract: Esterases and lipases have been studied in a number of fungi, though very little is known about esterases from Aureobasidium pullulans especially from the African tropics. In this study, forty-two Zimbabwean isolates were screened for lipase activity on tributyrin agar. Extracellular esterase activities of seven selected isolates were studied under varying conditions using para-nitrophenol acetate as substrate. Twenty isolates (48%) showed lipolytic activity; sixteen showed negative results for lipase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Os maiores halos de degradação, constatados através da análise dos experimentos realizados, apontaram que os substratos utilizados para a avaliação da enzima lipase eram os que sofriam maior hidrólise, apresentando índices enzimáticos de até 6,9 (tabela 2). Resultados bem diferentes dos encontrados por Kudanga et al 2007 CONCLUSÃO A bioprospecção enzimática inicial constitui-se em uma etapa primária para a caracterização do potencial enzimático dos isolados avaliados. Sendo assim, os isolados que foram identificados como promissores para a produção das diversas enzimas testadas, especialmente as lipolíticas, serão posteriormente avaliados com relação ao aperfeiçoamento das condições de cultivo para otimizar o processo de produção e ainda contribuir com o possível desenvolvimento e produção de novas enzimas hidrolíticas, as quais poderão vir a se tornar novas alternativas às enzimas hidrolíticas atualmente comercializadas e utilizadas em diferentes processos biotecnológicos e industriais.…”
Section: Resultsunclassified
“…Os maiores halos de degradação, constatados através da análise dos experimentos realizados, apontaram que os substratos utilizados para a avaliação da enzima lipase eram os que sofriam maior hidrólise, apresentando índices enzimáticos de até 6,9 (tabela 2). Resultados bem diferentes dos encontrados por Kudanga et al 2007 CONCLUSÃO A bioprospecção enzimática inicial constitui-se em uma etapa primária para a caracterização do potencial enzimático dos isolados avaliados. Sendo assim, os isolados que foram identificados como promissores para a produção das diversas enzimas testadas, especialmente as lipolíticas, serão posteriormente avaliados com relação ao aperfeiçoamento das condições de cultivo para otimizar o processo de produção e ainda contribuir com o possível desenvolvimento e produção de novas enzimas hidrolíticas, as quais poderão vir a se tornar novas alternativas às enzimas hidrolíticas atualmente comercializadas e utilizadas em diferentes processos biotecnológicos e industriais.…”
Section: Resultsunclassified
“…For example, the use of glycerol for growth requires the full breakdown of the triglyceride or cross‐linked triglycerides that are present in oil. Aureobasidium isolates, including an A. melanogenum isolate, are known to produce extracellular lipases (Kudanga et al, ; Leathers, Rich, Anderson, & Manitchotpisit, ; Liu, Chi, Wang, & Li, ; Wongwatanapaiboon et al, ), but they might not be able to break down all types of triglycerides because lipases act chemo‐specific and region‐specific. Also, triglyceride networks of cross‐linked triglycerides might inhibit binding and activity of lipases (Shogren, Petrovic, Liu, & Erhan, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of vegetable oils by fungi, including A. melanogenum (Leelaruji, Piamtongkam, Chulalaksananukul, & Chulalaksananukul, 2013), is frequently studied in the light of lipase production (Açikel, Erşan, & Açikel, 2011;Fadiloğlu & Erkmen, 2002;Najjar, Robert, Guérin, Violet-Asther, & Carrière, 2011). Generally, lipases are described as enzymes that catalyze the hydrolysis of triglycerides to glycerol and free fatty acids at an oil-water interface (Kudanga, Mwenje, Mandivenga, & Read, 2007;Treichel, Oliveira, Mazutti, Luccio, & Oliveira, 2010). In some studies, a vegetable oil was used as a sole carbon-based nutrient instead of a commonly used monomeric sugar and biomass growth in time was measured (Del Rio, Serra, Valero, Poch, & Sola, 1990;Molokwu & Okpokwasili, 1997).…”
mentioning
confidence: 99%
“…A similar result was reported that yeast extract [7], peptone and soy bean flour [6] stimulated the esterase/lipase production. Kudanga et al reported that casein was a good source for esterase production by Aureobasidium pullulans [21]. Corn steep liquor (waste product of corn processing) was reported to increase recombinant esterase production [22].…”
Section: Evaluation Of the Factors Affecting Esterase Activitymentioning
confidence: 99%